Adopting a Constraints-Led Approach to Enhance Skill Acquisition for Fast Bowlers in Grassroots Cricket - Mikael Jamil; Lewis Woolston; Simon Manthorpe; Saumya Mehta; Daniel Memmert; Allistair McRobert (CV. FOUNDAE, 2023)
In this quantitative study, a bespoke coaching drill was designed and tested over 16 weeks to improve the bowling accuracy of 6 participant seam bowlers. This experiment consisted of 6 male participants with a mean age of 19.5 ± 7.5, mean height (cm) of 184.75 ± 5.57, and mean weight (kg) of 78.05 ± 9.87. Due to the repeated measures experimental design, paired samples t-tests were conducted to assess the effectiveness of this coaching intervention and compare performances between the